Beta Convergence and Sigma Convergence: Evidence from Indonesian District-Level Data - Hendajany, Nenny; Saepudin, Didin; Suaesih, Ae (Jurnal Ekonomi Kuantitatif Terapan, 2017)
In this paper, we describe three things, (1) Evidence  of Beta -convergence’s existence in  Indonesian  districts-level data, (2) the reason of why Sigma -convergence may not accompany Beta -convergence, and (3) the demonstration to show that   Sigma -convergence cannot be detected at the districts  level across Indonesia using Indonesian  districts -level data that contains over 277 cross-sectional observations. If Indonesian individual provinces are considered separately, we find only 2 out of 25 provinces with detected Sigma -convergence. But also, in many cases statistically significant Sigma - divergence is found.
Keywords: Beta-convergence, Sigma-convergence and speed of convergence